Order estimates for the approximative characteristics of functions from the classes S_p,θ^Ω B(R^d) with a given majorant of generalized mixed modules of smoothness in the uniform metric - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the exact-order estimates of approximation for the classes S_p,θ^Ω B of functions of several variables defined on R^d in the norm of L_∞ (R^d) by entire functions of exponential type with supports of their Fourier transforms in the sets generated by the level surfaces of a function Ω.